2013
DOI: 10.1371/journal.pone.0080624
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pregnancy-Associated Malaria on Infant Malaria Infection in Southern Benin

Abstract: BackgroundInfants of mothers with placental Plasmodium falciparum infections at delivery are themselves more susceptible to malaria attacks or to infection in early life.Methodology/ Principal FindingsTo assess the impact of either the timing or the number of pregnancy-associated malaria (PAM) infections on the incidence of parasitemia or malaria attacks in infancy, we followed 218 mothers through pregnancy (monthly visits) up to delivery and their infants from birth to 12 months of age (fortnightly visits), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
2
36
0
1
Order By: Relevance
“…PAM has also been associated with a reduction in maternal antibody transfer to the foetus [33,34], hence increasing infant susceptibility to parasites [35,36]. Consistent with the notion that the type, timing, and the duration of exposure to the parasite in utero determine susceptibility to malaria, infections occurring during the third trimester are associated with increased risk of infection and clinical malaria during the first year of life according to another study in the province of Mono (South Benin) [24]. …”
Section: Methods: Search Strategy and Selection Criteriamentioning
confidence: 84%
“…PAM has also been associated with a reduction in maternal antibody transfer to the foetus [33,34], hence increasing infant susceptibility to parasites [35,36]. Consistent with the notion that the type, timing, and the duration of exposure to the parasite in utero determine susceptibility to malaria, infections occurring during the third trimester are associated with increased risk of infection and clinical malaria during the first year of life according to another study in the province of Mono (South Benin) [24]. …”
Section: Methods: Search Strategy and Selection Criteriamentioning
confidence: 84%
“…Initially the fetal liver followed by hematopoietic stem cell progenitors (HSC) in the bone marrow gives rise to lymphocytes and polymorphonuclear cells - neutrophils, eosinophils and mast cells. After 7 weeks of gestation T-cell progenitor cells expressing CD34 receptors migrate to the thymus and differentiate into mature subsets with CD4, CD8 and αβ T- cell receptors (TCRs) [9]. Minor portions of T-cell progenitors in the fetal liver possess γ/δ TCRs by 6–8 weeks of gestation and do not migrate to the thymus for maturation.…”
Section: Development Of Cellular Immunity In Neonatesmentioning
confidence: 99%
“…Earlier studies also demonstrated that maternal infections occurring in the third trimester are strongly associated with an increased susceptibility both to parasitemia and to malaria attacks during infancy [9]. Placental infection with Plasmodium falciparum (causative agent of malaria) or parasite-derived antigens in utero activate cord blood antigen presenting cells (APC) and modulates cord blood cytokine responses to TLR ligation [10].…”
Section: Development Of Cellular Immunity In Neonatesmentioning
confidence: 99%
“…We focus on pregnant women and their households in Southern Benin as a case study to clarify how contextual factors can affect behavioral change practices concerning bed net use and maintenance. Pregnant women constitute a higher‐risk group who are more susceptible to the disease than the general population, as malaria is associated with maternal anemia, fetal growth retardation, low birth weight, and preterm delivery, all of which are high risk factors for perinatal death, morbidity, and mortality …”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women constitute a higher-risk group who are more susceptible to the disease than the general population, as malaria is associated with e280 maternal anemia, fetal growth retardation, low birth weight, and preterm delivery, all of which are high risk factors for perinatal death, morbidity, and mortality. 4,22 Although the literature devoted to the factors affecting the ownership and use of bed nets is extensive, the evaluation of bed net maintenance practices is a neglected area. The contribution of our research is to elucidate the challenges pregnant women and their households face in the maintenance and effective use of bed nets.…”
Section: Introductionmentioning
confidence: 99%